Analysis of patients hospitalized for AMI in emergency care in Pará: An analysis from 2011 to 2022 - Walfredo, Thinan Anthony Leão (2024)
Acute Myocardial Infarction (AMI) is a serious clinical condition that occurs due to interruption of the blood supply to the heart muscle. Thus, epidemiology plays a central role in understanding acute myocardial infarction. Therefore, the objective of this work was to determine the epidemiological profile of AMI, in the context of emergency care in Pará between 2012 and 2022. This is an epidemiological, cross-sectional, retrospective and descriptive study, with quantitative presentation, carried out based on the collection of secondary data from the Hospital Information System (SIH/SUS), according to CID-10-I21- IAM, available at the Department of Informatics of the Unified Health System (DATASUS). The Metropolitana II, Rio Caetés and Tapajós regions were the regions with the highest occurrence of deaths. Furthermore, males are predominant when it comes to being affected by this disease, and are also the gender with the highest number of deaths. Within this, it was found that hospitalizations were concentrated in individuals aged 60 or over, with 2021 being the year with the highest peak for these hospitalizations. During the period studied, high rates of hospitalizations due to AMI were observed in the integration regions of Pará: Tapajós, Rio Caetés and Metropolitana II. Death was more frequent in males and elderly people. While females had the highest mortality rate.